The displacement y(x,t) is given by the equation
The suitable solution of (1) is given by
"y(x,t) = (A cos lx + B sin lx)(C cos lat + D sin lat) -------(2)"
The boundary conditions are
"(i)\\ y(0,t) = 0,\\ for\\ t\\ge0. \\\\\n(ii)\\ y(\u2113,t) ,\\ for\\ t\\ge0. \\\\\n(iii)\\ y(x,0)=0\\ for\\ all\\ 0<x<i\\\\\n(iv)\\ [\\frac{\\delta y}{\\delta t}]_{t=0}=g(x)= \\begin{cases}\n \\frac{kx}{l} & 0<x<l \\\\\n \\frac{k(2l-x)}{l} & l<x<2l\n \\end{cases}"
Using (i) and (ii) in (2) , we get
"0 = A(Ccoslat + Dsinlat)" , for all "t \\ge 0."
Therefore, "A = 0"
Hence equation (2) becomes
"y(x,t) = B sinlx(Ccoslat + Dsinlat) ------------ (3)"
Using (ii) in (3), we get
"0 = Bsinl\u2113 (Ccoslat+Dsinlat)" , for all "t \\ge 0" , which gives "l\u2113 = n\\pi"
Hence, "l=\\frac{n \\pi}{\u2113}" , n being an integer.
Thus
"y(x,t)=Bsin \\frac{n \\pi x}{l}[Ccos \\frac{n \\pi at}{l}+Dsin \\frac{n \\pi at}{l}]-----------(4)"
Using (iii) in (4), we get
"0=Bsin \\frac{n \\pi x}{l}C"
Therefore, "C = 0"
Hence "y(x,t)=Bsin \\frac{n \\pi x}{l} \\cdot Dsin \\frac{n \\pi at}{l}=B_1sin \\frac{n \\pi x}{l} \\cdot Dsin \\frac{n \\pi at}{l}"
Where "B_1=BD"
The most general solution is
"y(x,t)=\\sum_{n=1}^\\infin B_nsin \\frac{n \\pi x}{l} \\cdot sin \\frac{n \\pi at}{l}---------(5)"
Differentiating (5) partially w.r.t t, we get
"\\frac{\\delta y}{\\delta t}=\\sum_{n=1}^\\infin B_nsin \\frac{n \\pi x}{l} cos \\frac{n \\pi at}{l} \\cdot \\frac{n \\pi a}{l}"
Using condition (iv) in the above equation, we get
"y_t(x,0)=g(x)= \\begin{cases}\n \\frac{kx}{l} & 0<x<l \\\\\n \\frac{2l-x}{l} & l<x<2l\n\\end{cases}"
Taking "\\frac{kx}{l},\\ 0<x<l" we get
"\\frac{kx}{l}=\\sum_{n=1}^\\infin B_n \\frac{n \\pi a}{l} \\cdot sin\\frac{n \\pi x}{l}\\\\ \ni.e\\ B_n \\frac{n \\pi a}{l}=\\frac{2}{l}\\int_0^1 f(x)\\cdot sin\\frac{n \\pi x}{l}dx\\\\\ni.e\\ B_n =\\frac{2}{n \\pi a}\\int_0^1 f(x)\\cdot sin\\frac{n \\pi x}{l}dx=\\frac{2}{n \\pi a}\\int_0^1 \\frac{kx}{l}\\cdot sin\\frac{n \\pi x}{l}dx= \\frac{2}{n \\pi a}\\int_0^1 \\frac{kx}{l}d[\\frac{-cos\\frac{n \\pi x}{l}}{\\frac{n \\pi x}{l}}]\\\\\n= \\frac{2}{n \\pi a}\\{\\frac{kx}{l}d[\\frac{-cos\\frac{n \\pi x}{l}}{\\frac{n \\pi x}{l}}]-\\frac{k}{l}[\\frac{-sin\\frac{n \\pi}{l}}{\\frac{n^2 \\pi^2 }{l}}]\\}=\\frac{2}{n \\pi a}\\{\\frac{-2cos\\ n\\pi+2}{\\frac{n^3 \\pi^3 }{l^3}}\\}=\\frac{2}{n \\pi a} \\cdot \\frac{2l^3}{n^3 \\pi^3}\\{1-cos\\ n\\pi\\}\\\\\ni.e\\ B_n =\\frac{4l^3}{n^4 \\pi^4 a}\\{1-(-1)^n\\}\\\\\nor\\\\\nB_n= \\begin{cases}\n \\frac{8l^3}{l} & if\\ n\\ is\\ odd \\\\\n 0 & if\\ n\\ is\\ even\n\\end{cases}\\\\\n\n\\therefore\\ solution\\ is\\\\\ny(x,t)=\\frac{8l^3}{n^4a}\\sum_{n=1}^\\infin \\frac{1}{(2n-1)^4}\\sin\\ \\frac{(2n-1)\\pi a t}{l}\\sin\\ \\frac{(2n-1)\\pi x}{l},\\ \\forall\\ 0<x<l--->Answer"
Taking "\\frac{k(2l-x)}{l},\\ l<x<2l" we get
"\\frac{2kl-kx}{l}=\\sum_{n=1}^\\infin B_n \\frac{n \\pi a}{2l} \\cdot sin\\frac{n \\pi x}{2l}\\\\ \ni.e\\ B_n \\frac{n \\pi a}{l}=\\frac{2}{l}\\int_l^{2l} g(x)\\cdot sin\\frac{n \\pi x}{2l}dx\\\\\ni.e\\ B_n =\\frac{2}{n \\pi a}\\int_l^{2l} g(x)\\cdot sin\\frac{n \\pi x}{2l}dx=\\frac{2}{n \\pi a}\\int_l^{2l} \\frac{2kl-kx}{l}\\cdot sin\\frac{n \\pi x}{2l}dx= \\frac{2}{n \\pi a}\\int_l^{2l} \\frac{2kl-kx}{l}d[\\frac{-cos\\frac{n \\pi x}{2l}}{\\frac{n \\pi x}{2l}}]\\\\\n= \\frac{2}{n \\pi a}\\{\\frac{2kl-kx}{l}d[\\frac{-cos\\frac{n \\pi x}{2l}}{\\frac{n \\pi x}{2l}}]-\\frac{2kl-k}{l}[\\frac{-sin\\frac{n \\pi}{2l}}{\\frac{n^2 \\pi^2 }{2l}}]\\}=\\frac{2}{n \\pi a}\\{\\frac{-2cos\\ n\\pi+2}{\\frac{n^3 \\pi^3 }{4l^3}}\\}=\\frac{2}{n \\pi a} \\cdot \\frac{8l^3}{n^3 \\pi^3}\\{1-cos\\ n\\pi\\}\\\\\ni.e\\ B_n =\\frac{16l^3}{n^4 \\pi^4 a}\\{1-(-1)^n\\}\\\\\nor\\\\\nB_n= \\begin{cases}\n \\frac{32l^3}{l} & if\\ n\\ is\\ odd \\\\\n 0 & if\\ n\\ is\\ even\n\\end{cases}\\\\\n\n\\therefore\\ solution\\ is\\\\\ny(x,t)=\\frac{32l^3}{n^4a}\\sum_{n=1}^\\infin \\frac{1}{(2n-1)^4}\\sin\\ \\frac{(2n-1)\\pi a t}{l}\\sin\\ \\frac{(2n-1)\\pi x}{l},\\ \\forall\\ l<x<2l-->Answer"
Comments
Leave a comment